PENGEMBANGAN MULTIMEDIA INTERAKTIF “CAREER PLAN” UNTUK PERENCANAAN KARIER SISWA DI TINGKAT SEKOLAH MENENGAH ATAS - Nurul Maghfiroh; Heri Saptadi Ismanto; Padmi Dhyah Yulianti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The implementation of guidance and counseling services in the classroom is still dominated by lecture methods with less attractive whiteboard media, thus reducing student engagement and interest in learning. Therefore, innovative and interactive learning media are needed to support the implementation of guidance and counseling services. This study aims to develop and determine the feasibility and practicality of interactive multimedia Career Plan as a supporting medium for career guidance services for high school students. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 1 media expert, 1 material expert, 1 practitioner (guidance and counseling teacher), and 30 students of grade XI-2 SMA Institut Indonesia Semarang who were involved in a limited trial. The research instruments were expert questionnaire validation and user response questionnaire analysis, while the data technique used quantitative descriptive analysis based on the feasibility percentage. The results showed that interactive multimedia Career Plan obtained a feasibility percentage from media experts of 97% and material experts of 86,1%, while the practicality level based on the responses of guidance and counseling teachers was 100% and students was 98,3%. These findings indicate that the interactive multimedia Career Plan is feasible and practical for use as a career guidance service. This research contributes to the development of interactive multimedia-based guidance and counseling media that can support career services in a more engaging and systematic manner.